Women's Participation in Waste Management (A Case Study in Cileles Village, Jatinangor District, Sumedang Regency) - Virna Husna Nurfaizah; Rina Hermawati; Hardian Eko Nurseto (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2025)
This study investigates women’s participation—particularly that of housewives—in household waste management in Cileles Village, Jatinangor District, Sumedang Regency. It aims to understand how cultural norms, gender roles, and access to various forms of capital influence environmental practices at the domestic level. Using Pierre Bourdieu’s theoretical concepts of habitus, and capital (social, cultural, economic, and symbolic), the research employs a qualitative case study approach involving semi-structured interviews, participant observation, and documentation. Fourteen informants, including housewives, a TPS3R officer, and a village official, were selected purposively. The findings reveal that women’s participation is not only rooted in practical routines, but also embedded in long-standing cultural values and gendered socialization processes. Factors such as religious beliefs, inherited habits, and social networks support active participation, while economic limitations, limited infrastructure, and weak village regulation serve as inhibiting factors. This study highlights the need to recognize women’s environmental agency as a product of social structures, and recommends more inclusive and culturally grounded waste policies that empower women at the household level.